Marketing is a Positive Force in Contemporary Society: Case of Holland & Barrette Social Campaign - Algarni, Ohoud Mohammed (Journal of Economic, Administrative and Legal Sciences, 2025)
Objectives: This essay discusses and investigates marketing’s positive contribution to contemporary society as a force that leads to a better life. Also, targeting consumption is primarily to be modified by applying marketing techniques to yield desirable outcomes for all stakeholders. This will be reflected in businesses and society while paying attention to the challenges of limited marketing scope and other ethical considerations. Methods: a case study of the marketing concept as a whole and chosen approaches to demonstrate marketing’s positive impact on contemporary society, that illustrate the abilities and opportunities of marketing in making a behavioral change, with an example of a health corporation practicing social and sustainable marketing. Results: A positive impact on society can be achieved and maintained by taking advantage of marketing. Besides, future marketing efforts must consider more positive and supportive customer experiences to guarantee that the required behavioral outcome is sustained. While previous research investigated several aspects of social marketing, it fails to engage all diminutions that affect consumers’ behavioral change process, such as limiting studies on gender age, or culture group alongside greater involvement of policymakers in social marketing. Conclusions: Marketing practices and concepts may achieve positive change in society through applying social and sustainable marketing approaches From my perspective, appropriate employment of marketing techniques has significant potential to lead consumer behavior through an accurate and precise understanding of drivers and barriers of this behavior and create proper ethical and sustainable values that attract them to the desirable behavior.